If the shoe fits - Mlynowski, Sarah (New York : Scholastic Press, 2013)
On their second adventure through the magic mirror Abby and Jonah find themselves in the Cinderella fairy tale-- and that is when things start to go really wrong.
Keywords: Cinderella (Legendary character) -- Juvenile fiction; Fairy tales; Magic mirrors -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction